pH, WATER AND FAT CONTENT ANALYSIS OF INTEGRATED FORMULATION OF HERBS AND SPICES IN TYPICAL SIMALUNGUN “TINUKTUK” - Marini Damanik; Risti Rosmiati; Tyas Permatasari; Syarifah Ayuni; Tia Aulia Surbakti (Universitas Negeri Medan, 2022)
The use of spices and herbs is a functional food product that is believed to be efficacious for health and can increase the body's immunity or is usually called an immunomodulator. Tinuktuk has very good properties for the health of the body. By warming the body and also counteracting free radicals with antioxidant activity. This study aims to determine the optimization of the dose of the main components of red ginger and black pepper to produce Tinuktuk with high nutritional value by preparing with an oven. The process in this method uses the percentage of the ratio variation of 70:30, 60:40, 50:50, 40:60, and 30:70. Then, the quality of the tinuktuk was tested, namely: the pH, moisture and fat content. The oven method showed that the pH values from the ratio of 70:30, 60:40, 50:50, 40:60, and 30:70 were 6.15, 6.25, 6.25, 6.25, 6,3, respectively. Beside, for the water content was 56.61%, 54.68%, 54.065%, 49.395%, 45.265% and fat content was 15.52%, 18.35%, 15.46%, 19.39%, 16.50%.@font-face font-family:"Cambria Math"; panose-1:2 4 5 3 5 4 6 3 2 4; mso-font-charset:0; mso-generic-font-family:roman; mso-font-pitch:variable; mso-font-signature:-536869121 1107305727 33554432 0 415 0;@font-face font-family:Rosarivo; panose-1:2 11 6 4 2 2 2 2 2 4; mso-font-charset:0; mso-generic-font-family:auto; mso-font-pitch:auto; mso-font-signature:0 0 0 0 0 0;p.MsoNormal, li.MsoNormal, div.MsoNormal mso-style-unhide:no; mso-style-qformat:yes; mso-style-parent:""; margin:0cm; text-align:justify; line-height:115%; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman",serif; mso-fareast-font-family:"Times New Roman"; mso-ansi-language:IN; mso-fareast-language:EN-ID;.MsoChpDefault mso-style-type:export-only; mso-default-props:yes; mso-ansi-language:IN; mso-fareast-language:EN-ID;.MsoPapDefault mso-style-type:export-only; text-align:justify; line-height:115%;div.WordSection1 page:WordSection1;